2010
DOI: 10.1111/j.2041-210x.2010.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

A method for measuring the relative information content of data from different monitoring protocols

Abstract: Summary1. Species monitoring is an essential component of assessing conservation status, predicting effects of habitat change and establishing management and conservation priorities. The pervasive access to the Internet has led to the development of several extensive monitoring projects that engage massive networks of volunteers who provide observations following relatively unstructured protocols. However, the value of these data is largely unknown. 2. We develop a novel cross-data validation method for measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 27 publications
2
64
0
Order By: Relevance
“…Data collection protocols for VGI are either non-existent or not strictly enforced, e.g., with OSM data. In contrast, many citizen science projects in the area of biodiversity monitoring and conservation have well-defined data collection protocols that require user training and/or strong interaction with experts in the field [52]. In a sense, trying to cover this gap, the World Wide Web Consortium (W3C) and the Open Geospatial Consortium (OGC) have jointly published a draft document [53] on the best practices that should be followed when publishing spatial data on the web but there is still generally a lack of protocols in VGI.…”
Section: Introductionmentioning
confidence: 99%
“…Data collection protocols for VGI are either non-existent or not strictly enforced, e.g., with OSM data. In contrast, many citizen science projects in the area of biodiversity monitoring and conservation have well-defined data collection protocols that require user training and/or strong interaction with experts in the field [52]. In a sense, trying to cover this gap, the World Wide Web Consortium (W3C) and the Open Geospatial Consortium (OGC) have jointly published a draft document [53] on the best practices that should be followed when publishing spatial data on the web but there is still generally a lack of protocols in VGI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, opportunistic data typically consists of species presence locations, without information on species absences [8,26]. Munson et al [27] also found that the eBird opportunistic data had more uncertainty than the professionally collected North American Breeding Bird Survey (BBS) data. Due to these and other issues, many still consider opportunistic data to be low quality and unreliable for research and conservation planning purposes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sheer quantity and spatial extent of opportunistic data can provide researchers and policy makers with information on ecological trends that may otherwise go unnoticed due to the relative scarcity of professionally collected data [4,10]. Studies demonstrating the similar predictive results of models built on opportunistic data versus professional data further justify the use of opportunistic data [27]. A study conducted by Bried and Siepielski [10] also indicated that their presence-only opportunistic datasets contained identical patterns to that of presence-absence systematic datasets.…”
Section: Introductionmentioning
confidence: 99%
“…For many systems, the interesting and desirable information often lies within the uncommon data. The protocol for describing observations by participants is an important factor in measuring data quality (Munson et al, 2010). Munson et al also infer that the more unstructured the protocol, the higher the volume of data required to ensure a useful level of quality.…”
Section: Data Selection and Validationmentioning
confidence: 99%
“…Long-term monitoring, in a variety of geographic locations, gathers data about faunal activity and composition changes (Munson et al, 2010). The essential information to be monitored includes the presence, distribution, and abundance of faunal species.…”
Section: Introductionmentioning
confidence: 99%